Real-world safety and efficacy of omalizumab in patients with severe allergic asthma: A long-term post-marketing study in Japan. (August 2018) - Adachi, Mitsuru; Kozawa, Masanari; Yoshisue, Hajime; Lee Milligan, Ki; Nagasaki, Makoto; Sasajima, Takayoshi; Miyamoto, Terumasa; Ohta, Ken
Abstract: Background: Omalizumab (anti-IgE monoclonal antibody) is an approved add-on therapy for Japanese patients with severe allergic asthma. As directed by the Ministry of Health, Labor and Welfare Japan, a post-marketing surveillance (PMS) study on omalizumab was conducted between 2009 and 2017. Methods: The PMS observed safety and efficacy of omalizumab in patients treated with open-label omalizumab for 52 weeks (with optional 2-year extension period). Primary safety outcomes included incidence and severity of adverse events (AEs) and adverse drug reactions (ADRs). Primary efficacy outcomes included physician-assessed global evaluation of treatment effectiveness (GETE). Asthma-exacerbation-related events including requirement for additional systemic steroid therapy, hospitalization, emergency room visits, unscheduled doctor visits, and absenteeism were also evaluated. Results: Of 3893 patients registered, 3620 (age [mean ± SD] 59.3 ± 16.11 years) were evaluated for 52 weeks; 44.12% were aged ≥65 years and 64.45% were women. Overall, 32.24% reported AEs and 15.30% reported serious AEs. ADRs were seen in 292 (8.07%) patients. GETE results showed that the majority of patients experienced clinical improvements (58.29% at 16 weeks and 62.40% at 52 weeks). Nearly half of all patients (47.96%) were free from asthma exacerbations after therapy. Omalizumab also reduced all events related to asthma exacerbations. No specific ADRs were observed in the elderly population. Conclusions: This post-marketing study confirmed the clinically meaningful benefits of omalizumab in a majority of patients from Japan, and showed safety and efficacy in a real-life clinical setting to be consistent with previous reports.